(untitled) (Journal of the Digital Humanities Association of Southern Africa (DHASA), 2023)
The Third workshop on Resources for African Indigenous Languages (RAIL) was held (in person) on 30 November 2022 in Potchefstroom. RAIL was organized by the South African Centre for Digital Language Resources (SADiLaR). It was co-located with the 10th Southern African Microlinguistics Workshop, which took place 1 to 3 December 2022.